Monitoring and management of coastal hazards: Creation of a regional observatory of coastal erosion and storm surges in the pays de la Loire region (Atlantic coast, France). (1st November 2019) - Kerguillec, Riwan; Audère, Morgane; Baltzer, Agnès; Debaine, Françoise; Fattal, Paul; Juigner, Martin; Launeau, Patrick; Le Mauff, Baptiste; Luquet, Florent; Maanan, Mohamed; Pouzet, Pierre; Robin, Marc; et al.
Abstract: The OR2C (Observatoire Régional des Risques Côtiers) is a new observatory of coastal hazards located in the Pays de la Loire region on the Atlantic coast of France. It was created, in 2016, in a context of high regional vulnerability to coastal erosion and storm surges. The OR2C is in charge of monitoring nearly 400 km of coastline. Its major mission is to reinforce the scientific knowledge and improve tools for managing coastal hazards, reducing thus exposure to risks. Its set-up is also related to the need of a regional body to gather all parties involved in researching and managing coastal hazards, with the aim to create a regional dynamic of observation. The OR2C is based on original governance that creates a strong interface between academics and managers because it combines public institutions, research centers, decisional bodies, and operational bodies. This governance strengthens the dynamic of observation of coastal erosion and storm surges along the regional coast by improving the networking of the OR2C twenty-eight members. Monitoring strategy is based on an airborne LiDAR technology that provides annual topo-bathymetric data. One of the OR2C first actions was to establish an initial LiDAR acquisition survey (t0) in 2016 along 140 km of sandy coasts. The obtained data are updated every year and freely accessible to the coastal managers. The data are also used in an innovative toolbox of spatial analysis of coastal risks (MAp-RISC), which has an ability to map predisposition of coastal sectors exposed to coastal hazards. MAp-RISC provides several indicators to support decision-making, and could also be used in the future to update policies or strategic documents. Highlights: The main characteristics of the OR2C and its conditions of deployment. The main actions carried out since 2016 and their main outcomes. A unique tool for coastal hazard management (MAp-RISC). Regional coastal observatories are appropriate networks to fight against coastal risks. The OR2C is a new model of integrated regional collective action against coastal hazards.